FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN TERHADAP PEMBELIAN MINYAK GORENG KEMASAN DAN MINYAK GORENG CURAH DI KELURAHAN SEPANCAR LAWANG KULON - Puspitasari, Diah; Ogari, Putri Ayu; Lastinawati, Endang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study has directions to find out the factors that influence consumer decisions to purchase packaged cooking oil and bulk cooking oil in the Kelurahan Sepancar Lawang Kulon. This research method was carried out using a quantitative method where the research used binary logistic regression analysis. The data were obtained by interviewing the respondents in the sample using a questionnaire as a data collection tool that had been prepared beforehand. The results of this study are the factors that have a significant influence on consumer decisions on purchasing packaged cooking oil, namely the education variable (X2), income variable (X3), environmental influence variable (X5) and product quality variable (X6). Meanwhile, the variable price (X1) and the number of family members (X4) have no significant effect on the consumer's decision to purchase packaged cooking oil and bulk cooking oil.